2017
DOI: 10.4103/1008-682x.173445
|View full text |Cite
|
Sign up to set email alerts
|

Human semen quality and the secondary sex ratio

Abstract: The aim of this study was to evaluate the association between semen quality and the secondary sex ratio (SSR), defined as the ratio of male to female live births. Our study cohort comprised 227 male partners who were enrolled prior to conception in Michigan and Texas between 2005 and 2009, and prospectively followed through delivery of a singleton birth. The male partners provided a baseline and a follow-up semen sample a month apart. Semen analysis was conducted to assess 27 parameters including five general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Regarding association between SSR and parental stress, it is indicated that the variation in the SSR may result from alteration in the sex-selective preimplantation embryo loss [35]. As mechanisms affecting this alteration, sperm abnormality, reduced coitus and perturbations in the female reproductive tract caused by stress before preconception are considered [36, 37]. Similar reasons may affect the incidence of MZT.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding association between SSR and parental stress, it is indicated that the variation in the SSR may result from alteration in the sex-selective preimplantation embryo loss [35]. As mechanisms affecting this alteration, sperm abnormality, reduced coitus and perturbations in the female reproductive tract caused by stress before preconception are considered [36, 37]. Similar reasons may affect the incidence of MZT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current evidence is conflicting with other studies demonstrating no association between ART and SSR, but they are limited by their small sample sizes (Altman and Bland, 1995; Luke et al , 2009; Al-Jaroudi et al , 2018). This is further reflected in studies looking at semen parameters and SSR, with even fewer patients included (Bae et al , 2017; Malo et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, environmental endocrine-disrupting chemicals, for example, perfluoroalkyl substances (PFAS), bisphenol (BPA) and pesticides, have been shown to affect parental hormones and the secondary sex ratio through changes in sperm morphology and motility [2931]. When both parents are exposed to PFAS, BPA or other chemical substances, an excess of female births is observed that is significantly linked to only paternal chemical concentrations [3234]. Thus, endocrine-disrupting chemicals have clear anti-androgenic activities, as demonstrated in most animal studies [3537] and in adult humans [3840].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, endocrine-disrupting chemicals have clear anti-androgenic activities, as demonstrated in most animal studies [3537] and in adult humans [3840]. However, to determine whether the alterations of human sperm are correlated with low fertility and low sex ratio at birth, a direct relationship remains to be established between sperm quality and testosterone levels and a decrease in birth sex ratio [31, 34, 41].…”
Section: Introductionmentioning
confidence: 99%